REVIEW OF ISLAMIC LAW ON LULONGGANDA RITUAL CUSTOMS IN POST-HARVEST PROCESSION IN BENUA SUBDISTRICT OF SOUTH KONAWE REGENCY - A Arman (Profetika: Jurnal Studi Islam, 2022)
The lulongganda ritual is usually carried out by the people of Benua Village, this custom is an event that is carried out when the community has carried out the harvest and is about to open new land, then the community performs this ritual as a form of expression of prayer requests as well as their form of gratitude regarding the abundant harvest and without any disturbance, thanks to the implementation of the lulongganda ritual activity. In the implementation of the traditional lulongganda ritual, there are still many implementations that must be studied in Islamic law, therefore if we do something, it cannot be separated from the guidance and instructions that exist and are justified according to Islam, because religion is not a tool, but completely Religion does not oppose custom, as long as it does not conflict with the principles that have been justified by religion. The method used in this research is qualitative research using data collection methods, namely the observation method, interview method, and documentation method, then the type of research is field research. The results of this research reveal two things in the implementation process which are divided into two types, the implementation is by Islamic law and which is not by Islamic law, while the implementation is by Islamic law, namely: efforts to preserve the traditional lulongganda ritual, the lulo movement which has philosophical meaning in farming, preserving traditional arts and sports. While the implementation is not by Islamic law, namely: community expectations for the implementation of the lulongganda ritual, the implementation of mombaka okanda, the implementation of mosehe ndiolu.